Numerical Analyses for Grouped Wind Waves and Associated Long Waves on Composite Bottom Slopes - SOE, NAN MYAT; ASANO, Toshiyuki (PROCEEDINGS OF COASTAL ENGINEERING, JSCE, 2008)
This study investigates a coupling field of grouped wind waves and the resultant long waves on a bar type beach. The numerical results based on the Boussinesq equation have been compared with the analytical ones for the long waves generated by the time varying breaking point mechanism. The comparison aims at elucidating the mutual interaction process between the wind waves and long waves. The influence of the long waves on short waves is found to be significant for after-breaking zone through the alteration of eddy viscosity coefficient.